Formulating Sustainable Business Strategies For The Kratom Commodity: a Case Study of PT. ABC - Mokhamad Carnegie Trihandono; Harianto (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: Kratom is a growing business sector widely open for exploration. Indonesia, as a tropical country well-suited for kratom cultivation, requires a deeper understanding of the kratom industry in order to develop it into a competitive national commodity. Such development has the potential to contribute significantly to Indonesia’s economic growth and global trade positioning. The limited supply and growing market demand pose significant challenges for kratom entrepreneurs in Indonesia. Despite the growing demand and industry, the price of kratom in Indonesia has significantly declined over the past five years. PT ABC is one of the local kratom production company located close to Kratom’s cultivated area in West Borneo with a small capital and stagnant growth in the middle of growing number of new entrants.Purpose: This study aims to identify global challenges in the Indonesian kratom industry and to analyze the internal factors faced by private company (PT ABC), an important player in the kratom commodity sector, in order to formulate an effective business strategy.Design/methodology/approach: This research using a qualitative data extracted from PT ABC internal interview and questionnaire answered by experts and PT ABC’s stakeholder. The research utilizes Value Chain Analysis to identify internal factors and Porter's Five Forces to assess external factors. IFE EFE as input stage, SWOT analysis in the matching stage. Quantitative Strategic Planning Matrix (QSPM) for priority selection.Findings/Result: PT ABC faces several challenges that must be addressed in order to adapt to the rapidly growing global kratom industry. Based on this research, the company’s internal and external factors was identified, analyzed and extracted to several strategies to sustain PT ABC’s business.Conclusion: PT ABC recognizes that consistency and the quality of raw materials are key to the growth of the kratom business in Indonesia.Originality/value (State of the art): This research is the first to explore and analyze the business strategy of kratom commodity specifically at the private company level in Indonesia Keywords:  business strategy formulation, indonesian kratom industry, kratom export industry, kratom price volatility, mitragyna speciosa